Wszechmoc w płaszczu niemocy. Sprawiedliwość Boża w perspektywie chrystologicznej według Josepha Ratzingera/Benedykta XVI - Szymik, Jerzy (Verbum Vitae, 2014)
Christology is the key to understand God’s justice. Jesus – the Son who is one in substance with His Father – shows what God’s justice is and how different it is from men’s rules. God overcomes the logic of repayment, a suitable reward or deserved punishment, not through ignoring or excluding them, but through omnipotent love that makes Him assume the burden of responsibility and pay the price of Salvation. Incarnation of the Son of God, which leads Him inevitably to death and sacrifice of His life, redeeming the sense and intentions of all the previous sacrifices, becomes an expression of God’s justice. It returns a man to God as His possession and restores the image and the likeness of God in us. Paradoxically, justice that does not reveal itself through power and authority, but through love and sacrifice, turns out to be omnipotent, since it is redemptive. As such, through its excess, it establishes the kingdom of God and becomes a criterion of Christian ethos.